Pancasila Law State As An Instrument Of Indonesian Legal Politics: Efforts To Achieve A Just Indonesian Legal State - David Aprizon Putra; Nadia Veronica (Fakultas Hukum Universitas Lampung, 2022)
The law is actually present for humans, and not the other way around. This means that the law must be able to meet the human needs that are purposeful and boil down to the end of the whole substantive justice. Pancasila has accommodated that spirit as a whole, the second and fifth precepts are the two. Precepts of Pancasila expressly carry the spirit of justice as one of its main pillars. This normative juridical paper uses 2 research approach methods, namely the statute approach and he historical approach. The data used in this study are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials that are processed through 3 phases of processing data, namely data reduction, presentation and verification. Law enforcement, especially judges, have an important role in carrying out and building the legal structure of the Pancasila Law State, one of the main spearheads is social justice (justice for people) with rule breaking efforts. The spirit that law enforcement should have should not be solely according to the legal way but rather refer to the reasonable way. The legislators also play an important role, the stages and process of legislation are one part of the frame of the fundamental structure of the Pancasila Law State because at thes tage of the spirit of the regulation is formed.